Web information systems engineering -- WISE 2017. 18th International Conference, Puschino, Russia, October 7-11, 2017, Proceedings /: 18th International Conference, Puschino, Russia, October 7-11, 2017, Proceedings. Part I : (2017) - Unknown
No abstract available